Studies on Antimicrobial Activity of Bacillus Species isolated from soil samples against Multi-Drug resistant Enteric Bacteria - Barate, Dipali L. (International Journal of Scientific Research in Biological Sciences, 2021)
Bacillus species is one of the largest sources of bioactive natural products exhibiting a wide range of antibiotic activities. Antibiotics have been used against various infectious bacteria and fungi for over many years. The increase in the resistance amongst enteric bacteria limits the existing options of antibiotics. In the present study, resistance was highest among the E. coli (73.33%) followed by K. pneumoniae (59.09%), S. typhi (57.14%) and P. vulgaris (33.33%). 17 Bacillus spp. isolated from soil samples includes Bacillus subtilis, Bacillus amyloliquifacience and Bacillus licheniformis. It was found that isolate BS7, BS3 and BS1 showed prominent antimicrobial activity against tested MDR enteric bacteria.